New lenses for a new future. Why science needs theology and why theology needs science - Buitendag, Johan (HTS teologiese studies, 2023)
The ecological crisis almost forces different disciplines to search together for a better world.We all share one earth: the closer we reach a certain point, the closer we also come together. This places the paper amid the so-called science and religion dialogue in which theology increasingly takes cognisance of empirical research and scientific data. On the other hand, sciences are becoming increasingly aware of the need to transcend their evidential limitations to find a comprehensive paradigm.This paper will apply an exemplary methodology by selecting the eco-theology of Jürgen Moltmann as a theologian who takes relevant results of scientific ecological research seriously. The Club of Rome, on the other hand, is an example of social (and natural) sciences urging to find a new inclusive paradigm for a world in peril.The juxtaposition of theology and science provides the need for a new value system emerging in social sciences. Randers makes clear that the culture of consumerism had to be replaced by cultural elements that provide substantial longer-term satisfaction and increase well-being.The latest report of the Club of Rome (2022) and Moltmann’s latest two titles on this topic (2019 and 2020) have been integrated into the argument and previous publications of the author.Contribution: This exemplary approach contributes to a scientifically grounded and biblically founded eco-theology. The two exponents of science and eco-theology provide the much-needed vocabulary for each other. The Earth Charter, one could add, provides a grammar for the engagement of eco-theology and environmental science.